Moving beyond passive separations - McCutcheon, Jeffrey R.; Ostwal, Mayur; Zhang, Mi (Nature materials, 2022)
A composite membrane that contains porous organic cages is shown to be dynamic, with pore aperture diameter controlled by solvent allowing for graded molecular sieving.